Significant difference in active metabolite levels of ginseng in humans consuming Asian or Western diet: The link with enteric microbiota. (13th October 2016) - Wan, Jin‐Yi; Wang, Chong‐Zhi; Zhang, Qi‐Hui; Liu, Zhi; Musch, Mark W.; Bissonnette, Marc; Chang, Eugene B.; Li, Ping; Qi, Lian‐Wen; Yuan, Chun‐Su
Abstract: After ingestion of ginseng, the bioavailability of its parent compounds is low and enteric microbiota plays an important role in parent compound biotransformation to their metabolites. Diet type can influence the enteric microbiota profile. When human subjects on different diets ingest ginseng, their different gut microbiota profiles may influence the metabolism of ginseng parent compounds. In this study, the effects of different diet type on gut microbiota metabolism of American ginseng saponins were investigated. We recruited six healthy adults who regularly consumed different diet types. These subjects received 7 days' oral American ginseng, and their biological samples were collected for LC‐Q‐TOF‐MS analysis. We observed significant ginsenoside Rb1 (a major parent compound) and compound K (a major active metabolite) level differences in the samples from the subjects consuming different diets. Subjects on an Asian diet had much higher Rb1 levels but much lower compound K levels compared with those on a Western diet. Since compound K possesses much better cancer chemoprevention potential, our data suggested that consumers on a Western diet should obtain better cancer prevention effects with American ginseng intake compared with those on an Asian diet. Ginseng compound levels could be enhanced or reduced via gut microbiota manipulation for clinical utility.